Biodegradability study on the bioplastic derived from banana peel fruit waste with various ripening stages / Nur Azfira Azizan - Azizan, Nur Azfira (2022)
Bioplastic is currently being used to replace synthetic plastic utilized in food packaging. Bioplastic can be derived from a bio-based product such as banana peel which has a high biodegradation rate. In order to produce bioplastic which can be degraded easily by different types of soil and a good ripening stage must be chosen. The objectives of this research are to evaluate the effect of different types of soil and soil burial time on biodegradability of the films and to analyze the physical appearance of bioplastic derived from various banana ripening stages due to biodegradation process. In this research, bioplastics from the unripe, ripe and overripe peel of Musa acuminata x balbisiana (ABB) cv. Awak and Musa acuminata (AAA) cv. Berangan were used to analyze the biodegradation rate by means of weight loss. A biodegradability study of the bioplastic produced was conducted and a few variables such as different types of soil which are garden soil with loam (GL) and garden soil with loamy sand (GLS) and soil burial time were evaluated in depth. Moreover, the bioplastic films before and after buried in soil were also analyzed by sensory test and microscopic test. This research shows bioplastic from ripe peel has the highest weight loss (0.0834 g) compared to unripe peel (0.1446 g) and overripe peel (0.2526 g) when buried in GLS due to the increased sugar content in the ripe peel that promotes microbial activity as well as high moisture content and fine texture of the soil. The cross-view of bioplastic film also shows there is a biodegradation process occurred where the microstructure of the bioplastic film is irregular after being buried in the soil.